PERBANDINGAN EKSPRESI EMOSI PADA MAHASISWA YANG BERASAL DARI PESISIR PANTAI DENGAN YANG BERASAL DARI PEGUNUNGAN DI BANTEN BARAT (STUDI AWAL KONSELING MULTIKULTURAL PADA MAHASISWA PGSD UPI KAMPUS SERANG) - Ima Ni’mah Chudari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
The problem of this research was that there was a difference expression of anger between the societies who came from mountainous area (Pandeglang and Lebak) and western seashore area (Serang and Cilegon, Serang Regency) in Banten province. This might happened because they had different basic culture. Because of this phenomena, this reseach was aimed to know: 1) How is the basic emotional expression (including the feeling of anger, hate, scare, happy, sad, and surprise) of students in PGSD UPI Serang? 2) Was there any different expression of anger between between the societies who came from mountainous area and western seashore area? The research design was descriptive qualitative research. The technique of collecting the data used by the researcher was through observing and giving questionnaire. Observing was done to the both groups of students by watching out their expression when watching a film under the title “The Ride”. Then, the questionnaire was distributed to them to know the description of their emotional feeling. From observasion to both groups of students, it was found that there was no different expression of anger between the societies who came from mountainous area (Pandeglang and Lebak) and western seashore area (Serang and Cilegon, Serang Regency) in Banten province, and expression is basicly universal (including the feeling of anger, hate, scare, happy, sad, and surprise).Kata kunci: emosi, ekspresi emosi, budaya, konseling multikultural